2019
DOI: 10.1108/jcmars-01-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Service fairness and customer satisfaction

Abstract: Purpose The purpose of this paper is to investigate the relationship between service fairness and customer satisfaction, and test the mediation role of customer psychological empowerment in this relationship. Design/methodology/approach A cross-sectional empirical study is designed to test the research model. Customers of retail bank in South China are surveyed. Regression analysis and structural equation model analysis are done with SPSS 21.0 and LISREL 8.72 separately. Findings The results indicate that:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…In addition, this study's findings are consistent with the findings of earlier studies related to individual perception of fairness in the organization conducted by Waribo et al (2020) in Nigeria and service fairness perception of consumers conducted by Han et al (2019) in China. The result of the study conducted by Waribo et al (2020) depicted that all four dimensions of fairness have a significant positive influence on employee perception, whereas a study conducted by Han et al (2019) suggested that distributive, procedural, and interpersonal fairness have a significant positive influence on customer psychological empowerment. In contrast, there is no influence on informational fairness.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, this study's findings are consistent with the findings of earlier studies related to individual perception of fairness in the organization conducted by Waribo et al (2020) in Nigeria and service fairness perception of consumers conducted by Han et al (2019) in China. The result of the study conducted by Waribo et al (2020) depicted that all four dimensions of fairness have a significant positive influence on employee perception, whereas a study conducted by Han et al (2019) suggested that distributive, procedural, and interpersonal fairness have a significant positive influence on customer psychological empowerment. In contrast, there is no influence on informational fairness.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study are also in line with the findings of earlier studies conducted by Waribo et al (2020) that all four dimensions of fairness significantly positively influence employee behaviour outcomes via employee perception. Moreover, the study conducted by Han et al (2019) suggested that distributive, procedural, and interpersonal fairness significantly positively influence customer satisfaction via customer psychological empowerment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AR-based services service efficiency, the time needed or the degree of service personalization (Han et al, 2019).…”
Section: Fairness Perceptions Inmentioning
confidence: 99%